A mismatch between external debt finances and consumption cost in Nigeria - Cordelia Onyinyechi Omodero; Ben-Caleb Egbide; Joseph Ugochukwu Madugba; Benjamin Ehikioya (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study scrutinizes the influence of external obligation on the cost of living in Nigeria. In recent times, Nigeria has been tagged as the headquarters of world poverty due to the unaffordable cost of living that has resulted in all manner of crimes prevailing in the country. However, the role of foreign loans being contracted by the government in reducing consumption cost has become a concern, hence this investigation. This study made use of a secondary form of statistical records covering the period 2000-2018. The result of the data analysis has shown that external debt does not improve consumption cost, but rather aids the rising cost of living in Nigeria. In a nutshell, the study suggests that the government should invest a large chunk of the borrowed funds into agriculture and local manufacturing for sufficient food supply and provision of goods and services at reasonable costs. This study recommends support for infant industries and entrepreneurship to reduce the consumption cost in the country. The study also encourages the government to seek debt rearrangement or outright revocation by the lending institutions and countries.
Keywords: 650; consumption cost; debt serving; exchange rate; external debt; finances